HYLA-LUCTUOSA, A NEW TREEFROG FROM SOUTHEASTERN BRAZIL (AMPHIBIA, HYLIDAE) - Pombal, J. P.; Haddad, CFB (Herpetologists League, 1993)
A new species of treefrog, Hyla luctuosa, is described from the Serra do Japi in southeastern Brazil. The new species is a member of the Hyla circumdata group characterized by large size, large tympanum, and rounded subarticular tubercles on the fingers. Descriptions of the tadpole and advertisement call and information on natural history are provided.
Keywords: ANURA; ATLANTIC FOREST; ADVERTISEMENT CALL; HYLA-LUCTUOSA NEW SPECIES; SOUTHEASTERN BRAZIL; TADPOLE